+0  
 
0
136
3
avatar+862 

Find the length of GJ

 May 10, 2021
 #1
avatar+121055 
+2

Secant-Chord Theorem

 

JH  ( JH +  HG)  =  JK  ( JK + KL)

 

6 ( 8 + HG)  =  5 ( 5 + 7)

 

6 ( 6 +HG)  =  5 (12)

 

6 ( 6 + HG)  =  60       divide through by 6

 

6 + HG  =  10

 

HG  =  10  -  6   =   4

 

So

 

GJ  = HG  + JH   =   4 + 6   =   10

 

 

cool cool cool

 May 10, 2021
 #2
avatar+862 
+2

thanks!

AnimalMaster  May 10, 2021
 #3
avatar+121055 
+1

No problem  !!!!

 

 

cool cool cool

CPhill  May 10, 2021

28 Online Users

avatar